Factors controlling particle number concentration and size at metro stations. (May 2017) - Reche, C.; Moreno, T.; Martins, V.; Minguillón, M.C.; Jones, T.; de Miguel, E.; Capdevila, M.; Centelles, S.; Querol, X.
Abstract: An extensive air quality campaign was performed at differently designed station platforms in the Barcelona metro system, aiming to investigate the factors governing airborne particle number (N) concentrations and their size distributions. The study of the daily trends of N concentrations by different size ranges shows that concentrations of N0.3–10 are closely related with the schedule of the metro service. Conversely, the hourly variation of N0.007–10 (mainly composed of ultrafine particles) could be partly governed by the entrance of particles from outdoor emissions through mechanical ventilation. Measurements under different ventilation settings at three metro platforms reveal that the effect on air quality linked to changes in the tunnel ventilation depends on the station design. Night-time maintenance works in tunnels are frequent activities in the metro system; and after intense prolonged works, these can result in higher N concentrations at platforms during the following metro operating hours (by up to 30%), this being especially evident for N1–10 . Due to the complex mixture of factors controlling N, together with the differences in trends recorded for particles within different size ranges, developing an air quality strategy at metro systems is a great challenge. When compared to street-level urban particles concentrations, the priority in metro air quality should be dealing with particles coarser than 0.3 μm. In fact, the results suggest that at narrow platforms served by single-track tunnels the current forced tunnel ventilation during operating hours is less efficient in reducing coarse particles compared to fine. Highlights: Particle number size distribution recorded at 9 different metro platforms. Mean N0.3–10 correlate with the depth of the platforms in the old metro lines. UFP may be partly governed by outdoor emissions through mechanical ventilation. At operating hours, coarse particles less abated than UFP by tunnel ventilation. The control of coarse particles should be a priority at the metro system.